Aspiration to develop province, happy country - new highlights in the document of the 13th party congress - Bùi Thị Bích Thuận, (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
The 13th Party Congress is a political event of special historical significance, an important milestone in the development process of our Party and our country. For the first time, in the theme of the Congress and throughout the content of the document, it always mentions "aspiration to develop a prosperous and happy country". This is a very new point and an important point. The article aims to explain the theoretical and practical basis of this guiding point of view; thereby analyzing some basic solutions in the Document of the 13th Party Congress to arouse the aspiration to develop a prosperous and happy country; strives that by 2045, Vietnam will become a developed and high-income country.